Phylogenetic Affinity and Genome Structure Features of ctxAB– tcpA+ Vibrio cholerae from the Surface Waterbodies in the Territory that is Non-Endemic as Regards Cholera - L. V. Mironova (Проблемы особо опасных инфекций, 2020)
Objective is analyzing the origin of the ctxAB– tcpA+ Vibrio cholerae О1 El Tor strains isolated from the surface water bodies in the territory that is non-endemic of cholera; as well as investigating their phylogenetic relations to varying by epidemic significance groups of strains, based on the structure of housekeeping genes and whole genome structure. Materials and methods: we examined 25 V. cholerae strains, isolated in Siberia and Far East, including two ctxAB– tcpA+ strains from surface water sources (Altai Territory, 2011; Khabarovsk Territory, 2013). Phylogenetic analysis included genomes of 36 V. cholerae strains from GenBank. Multilocus sequence typing (MLST) was carried out based on dnaE, cat, lap, pgm, recA, gyrB, and chi genes; in silico MLST – adk, gyrB, metE, mdh, pntA, purM and pyrC genes. Reconstruction of phylogeny was performed based on the comparative analysis of core genome SNPs in PhyML 3.0. Results and discussion. MLST of ctxAB– tcpA+ V. cholerae О1 El Tor strains from the surface water bodies revealed that such strains form an individual genotype in the cluster of toxigenic strains and spontaneous mutants of toxigenic strains. According to results of in silico MLST, ctxAB– tcpA+ isolates belong to SТ75, common to US Gulf phylogenetic line. Based on SNP-typing, ctxAB– tcpA+ strains from the surface water sources were assigned to the group, originating from US Gulf V. cholerae, moreover isolate from Khabarovsk (2013) demonstrated high degree of genome homology with US Gulf-like strain from China (2009). For strains from Khabarovsk and China, we also showed the compositional identity of the pathogenicity island VPI-I and the presence of pandemicity island, VSP-1. The results testify to the fact that ctxAB– tcpA+ V. cholerae strains, isolated in Siberia and Far East, originate from the US Gulf phylogenetic line. Furthermore, taking into account the results of epidemiological analysis, we can deduce that these strains are imported ones.